Um diamante a ser lapidado: mulher em cargo de liderança nas comissões técnicas das equipes da superliga brasileira de voleibol feminino - série A - Silva, Tatiana Ribas da (2024)
When analyzing leadership positions in the global sports field, we encounter male dominance, which extends to various sectors of society. The objective of this research was to analyze why the inclusion of women in leadership roles in one of the largest volleyball competitions in the world, the Brazilian Women’s Volleyball Superliga – Série A, has been só unequal and inconsistent over the past 30 years. This research is qualitative and descriptive, utilizing interviews and an online semi-structured questionnaire to map the scenario of women’s volleyball in both youth and professional categories. A total of 52 individuals participated, distributed as follows: 40 members of the technical staffs of the under-18 teams in the 2023 edition of the Taça Paraná de Voleibol feminino; 10 members of the technical staffs of the teams competing in the 2023/2024 season of the Brazilian Women’s Volleyball Superliga – Série A; and 2 former coaches who worked in the Brazilian Women’s Volleyball Superliga – Série A between 1994 and 2023. A frequency analysis of the questionnaire/interview responses was conducted. The data were analyzed using IBM SPSS software, version 20.0 for Windows, and the main sociological theoretical framework used was Pierre Bourdieu’s Theory of Fields and Theory of Male Domination, with the concepts of male domination and symbolic violence to understand the relationship between the dominated and the dominant. Additionally, Marchi Júnior’s Analytical Model of Sport: 5 E’s was applied to complement the analysis. The results show that 70% of the technical staffs in the Taça Paraná and 90% in the Brazilian Women’s Volleyball Superliga – Série A are composed of men. Most professionals in the Taça Paraná are from the southern region of Brazil, while most in the Superliga are from the southeastern region. The majority of participants in both competitions are married and have children. All have a good academic level, with most having completed postgraduate studies (specialization). However, few women completed CBV training courses; in the Taça Paraná, most did not complete Level III, and only men completed Level IV. In terms of remuneration, women face greater salary inequality, being concentrated in the lower pay brackets in both competitions. Regarding years of experience, most men and women in the Superliga have less than five years of professional experience. Gender inequality reflects a combination of cultural, social, and institutional factors. Among these factors are the lack of recognition, support, and inclusive public policies, which perpetuate gender inequality in sports. Additionally, physical strength, the competitive environment, and the lack of opportunities and support are cited as barriers to women’s advancement in leadership positions. In conclusion, the research revealed male domination and symbolic violence, highlighting a “blockage” that limits the advancement of female leadership in volleyball. These findings underscore the need for future investigations and reinforce that women in leadership roles in volleyball are still a diamond in the rough, with potential yet to be fully developed.